0575 Validation of a Portable Monitoring for the Diagnosis of Obstructive Sleep Apnea: Electrocardiogram-based Cardiopulmonary Coupling. (12th April 2019) - Lu, Mi; Fang, Fang; Wei, Yongxiang
Abstract: Introduction: This study was to evaluate the diagnostic accuracy of the cardiopulmonary coupling (CPC) device, a limited-channel portable monitoring device for diagnosing obstructive sleep apnea (OSA) in patients suspected with sleep disordered breathing, in particular in those with cardiovascular diseases. Methods: 203 patients referred to the sleep medical center were enrolled in this study. All participants were monitored with CPC when receiving polysomnography (PSG). The results of 2 examinations were compared in the all and in subgroup combined with cardiovascular abnormalities. Results: A total of 179 subjects suspected with OSA were finally analyzed. According to apnea hyperpnea index (AHI), the area under ROC curve in the whole cohort patients was 0.79 (mild), 0.79 (moderate) and 0.86 (severe) respectively (all p<0.001). The Bland-Altman plots showed that PSG and CPC device were in good consistency in evaluating OSA and 92.7% (13/179) scatters were in the limits of agreement. For those with cardiovascular disease with different OSA severity, the area under the ROC curve was 0.86, 0.76 and 0.83, respectively (all p <0.0001), and 0.74, 0.85 and 0.91, respectively in patients without cardiovascular disease (all p <0.0001). And the Bland-Altman plots showed that the mean difference was -11.5 events/h and 92.4% (97/105) scatters were in the limits of agreement for the patients with cardiovascular conditions, and the mean difference was -11.4 events/h and 93.2% (69/74) scatters were in the limits of agreement for the patients without cardiovascular. Conclusion: The overall performance of CPC technique was acceptable to assess OSA in a highly suspected subjects, and thus it might act as an alternative tool to screen OSA patients. Furthermore, the utility of CPC technology for patients with cardiovascular disease with fair agreement, which can be a fast screen technology in those unable to be performed PSG. Support (If Any)